ALL-RUSSIAN CIVIL IDENTITY IN THE OFFICIAL DISCOURSE OF THE REPUBLICS OF NORTHERN CAUCASUS - E. S. Karsanova (Publishing House of the State University of Management, 2021)
The article considers the issue of formation of the all-Russian civil identity, actualized in the domestic political discourse. The paper reviews the phenomenon of identity as a dialogical and discursive phenomenon. In order to determine the main trends in the development of the North Caucasian republics, the author investigates regional practices of implementing the Strategy of State National Policy, internal political and inter-ethnic relations, migration processes. The study emphasizes the necessity of finding special formats of socio- political organization of the subjects of the Northern Caucasus region, expressing not only their local and ethno-cultural characteristics, but coping with the function of consolidation and co-optation of local communities in national socially and politically significant processes. As a result of the analysis of the problem of general civil identity generation the author concludes that these problems are primarily due to the contradictory dichotomy of identification processes that provoke competition and confrontation between ethnic and civil identities. In different objectively proposed circumstances the ambivalent manifestation of identity in the majority of Northern Caucasus peoples can act as a destructive, and a factor in the growth of All-Russian civil identity.